Tinjauan Yuridis terhadap Tindak Pidana Ujaran Kebencian (Hate speech), : Kekerasan dan Pornografi dalam Game online Dari Undang-Undang Nomor 1 Tahun 2024 Sebagaimana Perubahan Ke-2 Atas Undang-Undang Nomor 11 Tahun 2008 Tentang Informasi dan Transaksi Elektronik - Margreth Thatcer Appah; Bhisa Vitus Wilhelmus; Darius Antonius Kian (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The ease of access and availability of online game s on the internet opens up new opportunities as well as challenges. This challenge arises because not all online games are suitable for people to play. Many online games contain negative elements, such as violence, hate speech, and pornography. The provisions in Law No. 1 of 2024 on the Second Amendment to Law No. 19 of 2016 on the Amendment to Law No. 11 of 2008 on Electronic Information and Transactions are the main basis for countermeasures in cyberspace. The type of research the author uses is Normative Legal Research (library research). This research is also called a document study conducted by examining library and secondary materials, especially written regulations or other legal products. The results show that the rapid growth of online gaming has led to serious problems such as the spread of hate speech, bullying, and pornographic content. The lack of clarity in regulations makes it difficult to enforce the law against criminals in the online gaming realm. To overcome this problem, collaboration between various parties is needed, with an emphasis on increasing the capacity of law enforcement, developing digital forensic technology, improving regulations, and increasing legal awareness among the public.